PENGUATAN ALIH TEKNOLOGI PRODUKSI DI UKM SAMBEL PECEL, ANGGOTA JARINGAN USAHA SEKOTA BATU “GRAS” (Guyub Rukun Agawe Santoso) DI KOTA WISATA BATU - Siti Asmaul Mustaniroh (Journal of Innovation and Applied Technology, 2016)
ABSTRACT SMEs Echo Food and Rr Rahayu, located in Batu, produce peanut paste. Unfortunately, they has low efficiency and production because production facilities still manually. The long duration during milling process causes reducing time production. Therefore, the quality and quantity of the product cannot be maximal. The need for technological innovation over the production process will be able to improve the performance and quality of health functional beverage production. The results that have been achieved in the implementation of IbM activities include facilitating the transfer of technology in the form of milling machine and frying machine which has been applied by partners, guidance on improvement of production and management system includes quality control, GMP and log book for business management, and training, socialization and mentoring improved packaging design and marketing on-line. The results showed an increase in production efficiency with shorter time, increased quality packaging and products value is higher so that SMEs can increase profits.